CARACTERIZATION OF PROFISSIONALS OF ON UNIT OF HEALTH ABOUT DE INDICATION FÍSIC DE QUALITY OF LIFE (Fiep Bulletin - online, 2013)
This work intends to contribute with the reflection to about the quality of life and the functions played for the professionals of health and its characterization, more specifically in the service I publish Municipal theatre in the Unit of Health of Garden of the Penha, Victory, E.S., Brazil. One is to a study, descriptive and comparative matrix of longitudinal, almost experimental character, for being developed inside of the environment of work of the population to be investigated. The population of this study is of 81 participants, adults of both the sexes, distributed in 17 diversified categories and hours of working of 6 and 8 daily hours, reveals sufficiently significant taking in sight the number of employees who work in unit (120 employees), being that of these 81 seven is men and 51 women. Analyzing the results presented in the table, we can conclude that the studied population is composed of IMC above of the ideal esteem for the Americam Colloge (IMC 25). The average if keeps 2 points above (IMC 27), conhecidentemente with the one of the women who although to be above of the adequate one, still they meet in privileged situation in relation the men who are above still the women 1 point (IMC 28).
Keywords: Physical worker of the Health; Pointers Fistic; Quality of Life; Professionals of health.